Adaptation and relocation of built heritage : what can we learn from the urban transformations of Swedish mining towns? - Luciani, Andrea; Sjöholm, Jennie (Luleå tekniska universitet, Arkitektur och vatten, 2020)
In the arctic and subarctic region, climate change may require in the future the relocation of entire communities, with dramatic impacts on their built heritage. In northernmost Sweden, the two arctic mining towns of Kiruna and Malmberget are already experiencing similar disruption due to subsidence caused by mining. This paper investigates the actions implemented to mitigate the impacts of the ongoing urban transformations. Historic buildings and entire districts are demolished, documented or relocated, sometimes with the ambition to recreate historic environments. These controversial processes exemplify the scale and the level of the challenges and dilemmas that climate change will soon pose to historic environments. Can relocation preserve the complexity of an historic urban environment? How are decisions on what to save made? How do the loss and the relocation of heritage affect the local communities? Discussing and understanding it is crucial to make northern historic sites and communities more resilient.